The Effects of Antimicrobial Resistance and the Compatibility of Initial Antibiotic Treatment on Clinical Outcomes in Patients With Diabetic Foot Infection. (June 2023) - Saltoglu, Nese; Surme, Serkan; Ezirmik, Elif; Kadanali, Ayten; Kurt, Ahmet Furkan; Sahin Ozdemir, Meryem; Ak, Oznur; Altay, Fatma Aybala; Acar, Ali; Cakar, Zeynep Sule; Tulek, Necla; Kinikli, Sami; et al.
We aimed to determine pathogen microorganisms, their antimicrobial resistance patterns, and the effect of initial treatment on clinical outcomes in patients with diabetic foot infection (DFI). Patients with DFI from 5 centers were included in this multicenter observational prospective study between June 2018 and June 2019. Multivariate analysis was performed for the predictors of reinfection/death and major amputation. A total of 284 patients were recorded. Of whom, 193 (68%) were male and the median age was 59.9 ± 11.3 years. One hundred nineteen (41.9%) patients had amputations, as the minor (n = 83, 29.2%) or major (n = 36, 12.7%). The mortality rate was 1.7% with 4 deaths. A total of 247 microorganisms were isolated from 200 patients. The most common microorganisms were Staphylococcus aureus (n = 36, 14.6%) and Escherichia coli (n = 32, 13.0%). Methicillin resistance rates were 19.4% and 69.6% in S aureus and coagulase-negative Staphylococcus spp., respectively. Multidrug-resistant Pseudomonas aeruginosa was detected in 4 of 22 (18.2%) isolates. Extended-spectrum beta-lactamase-producing Gram-negative bacteria were detected in 20 (38.5%) isolates of E coli (14 of 32) and Klebsiella spp. (6 of 20). When the initial treatment was inappropriate, Klebsiella spp. related reinfection within 1 to 3 months was observed more frequently. Polymicrobial infection ( p = .043) and vancomycin treatment ( p = .007) were independent predictors of reinfection/death. Multivariate analysis revealed vascular insufficiency ( p = .004), hospital readmission ( p = .009), C-reactive protein > 130 mg/dL ( p = .007), and receiving carbapenems ( p = .005) as independent predictors of major amputation. Our results justify the importance of using appropriate narrow-spectrum empirical antimicrobials because higher rates of reinfection and major amputation were found even in the use of broad-spectrum antimicrobials.